PERAN KBIHU AR-RAUDHAH SINGGAHAN TUBAN DALAM PEMBINAAN HAJI MABRUR BERDASARKAN PERSPEKTIF UNDANG-UNDANG NOMOR 8 TAHUN 2019 - Nurul Hidayah; Fathonah K. Daud; Nur Puat (LP2M Universitas Ibrahimy, 2023)
This research is motivated by problems regarding the procedures for carrying out and departing for the Hajj/Umrah pilgrimage in Tuban, due to the lack of insight regarding the Hajj/Umrah pilgrimage. Thus, there is a need for a guide to arrive at the holy land, including how the pilgrimage was implemented by KBIHU Ar-Raudhah SinggahanTuban in terms of coaching when in the country. This research aims to determine whether the system for organizing the pilgrimage at KBIHU Ar-Raudhah has properly implemented Law Number 8 of 2019. This qualitative descriptive study uses observation, interviews, and documentation data collection techniques. This study's results indicate that the pilgrimage implementation at KBIHU Ar-Raudhah Singgahan Tuban is very good, and almost all the implementation of the pilgrimage at KBIHU Ar-Raudhah has implemented Law Number 8 of 2019. From this research, it is hoped that the implementation of the pilgrimage in Indonesia always Role, KBIHU Ar-RaudhahSinggahan, Law number 8 of 2019, pays attention to the standards set by the Government and always prioritizes the satisfaction of the congregation.